Dielectric relaxations in PVDF/BaTiO3 nanocomposites - Chanmal, Chetan; Jog, Jyoti Prakash (Express Polymer Letters, 2008)
The present work aims at the study of molecular relaxations in PVDF/BaTiO3 nanocomposites using broadband dielectric spectroscopy. The nanocomposites of PVDF with BaTiO3 ( 10-30% by wt%) are prepared using simple melt mixing method. In dielectric permittivity study, two relaxation processes are identified corresponding to the crystalline, glass transition in the PVDF/BaTiO3 nanocomposites. The peaks shift to higher frequencies as the temperature is increased. Electric modulus formalism is used to analyze the dielectric relaxations to overcome the conductivity effects at low frequencies. In M `' spectra two peaks are observed only at high temperature and low frequency whereas a single relaxation peak appears at low temperatures. The single relaxation peak appearing at low temperatures is the alpha(c) relaxation attributed to crystalline chain relaxation in PVDF and the second relaxation peak which appears only at high temperatures and at a frequency lower than alpha(c) relaxation is identified as MWS relaxation. The temperature dependence of alpha(c) relaxation and MWS relaxation follows Arrhenius type behavior.
Keywords: dielectric spectroscopy; Interfacial polarization; MWS relaxation; Nanocomposites